REVIEW OF THE USE OF DRONES AND NON-METRIC CAMERAS FOR THE PROVISION OF LARGE-SCALE GEOSPATIAL DATA ACCORDING TO BIG REGULATION NO. 1 OF 2020 - Rakuasa, Heinrich (Journal of Data Analytics, Information, and Computer Science, 2024)
Currently, the need for large-scale mapping for the entire territory of Indonesia is urgent. Therefore, accelerating the provision of large-scale Geospatial Data (DG) is essential for better spatial planning and regional development. The use of drone technology with non-metric cameras is starting to be used for the provision of large-scale DG. To regulate the use of drones and non-metric cameras, the Geospatial Information Agency issued the Head of Geospatial Information Agency Regulation No. 1 of 2020. The purpose of this paper will review the use of drones with non-metric cameras that have been regulated in the agency's regulations. The method used in this paper uses qualitative research with a data collection strategy or source using the literature method. The results show that the use of direct georeferencing in BIG Regulation No. 1 of 2020 has fulfilled the horizontal and vertical geometry accuracy requirements stipulated in BIG Head Regulation No. 6 of 2018 on Base Map Accuracy. The GSD value requirement in BIG Regulation No 1/2020 is too high compared to the GSD value requirement specified in the ASPRS Accuracy Standards for Digital Geospatial Data. This agency regulation is a standard / reference that must be met for all mapping industry players. Therefore, the implementation of this agency regulation requires further study to truly support the issue of accelerating large-scale mapping.